Influence Mechanism of Multi-dimensional Proximity on Cross-border Cooperative Innovation - Hui Wang (Forest Chemicals Review)
This paper takes the multi-dimensional proximity between cross-border cooperative organizations, that is, technical proximity, institutional proximity, cognitive proximity and relationship proximity as independent variables, so as to reflect the knowledge base, external support, breadth, depth and smoothness of information transmission among organizations in the process of cross-border cooperation. The theoretical model is constructed with cross-border search as the intermediary variable and cooperative innovation performance as the dependent variable. Structural equation model was used to test. This paper researches the impact of multi-dimensional proximity on cross-border cooperative innovation, and discusses the intermediary role of cross-border search in the relationship between multi-dimensional proximity and cooperative innovation performance.